Penyusunan Laporan Keuangan Sesuai dengan SAK-EMKM pada Toko Pupuk Muda Jaya di Kecamatan Payakumbuh - Izati Izati; Nini Sumarni (ARZUSIN, 2026)
Although the preparation of financial statements in micro, small, and medium enterprises (MSMEs) has received attention in various studies, studies that specifically discuss the design of financial statements in accordance with Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah (SAK EMKM) in businesses that still use simple recordkeeping remain limited. This study aims to analyze the financial recordkeeping system and to prepare financial statements in accordance with SAK EMKM at Toko Pupuk Muda Jaya. This study employed a qualitative approach with a case study design, involving the main informant, namely the business owner, who was selected through purposive sampling. Data were collected through observation, interviews, and documentation, and were then analyzed using descriptive qualitative analysis techniques through the stages of data reduction, data display, and conclusion drawing. The results showed that the financial recordkeeping carried out was still limited to cash inflows and cash outflows without clear account classification, so it was not yet in accordance with accounting standards. After being prepared based on SAK EMKM, the financial statements could be presented more systematically and comprehensively, including the statement of financial position, income statement, and notes to the financial statements. These findings contribute to the development of the concept of applying accounting standards in MSMEs while broadening understanding of the importance of preparing standardized financial statements. This study concludes that the implementation of SAK EMKM is important for improving the quality of MSMEs’ financial information and underscores the need for more systematic recordkeeping by business actors. The implications of this study include theoretical contributions to the development of the MSME accounting literature and practical contributions for business actors and related stakeholders, while also opening opportunities for further research on the implementation of digital-based accounting systems in MSMEs.